MENINGKATKAN PEMBELAJARAN DAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN DENGAN STRATEGI INQUIRI SOSIAL - Azmi, Shofiyatul; Roshidin, Roshidin (FKIP Universitas Wisnuwardhana, 2019)
This study aims to improve the learning process and learning achievement of PKn by applying social inquiry learning strategies. Social inquiry strategies are one of the learning strategies by systematically structured ways of thinking and ways to find out their own (inquiry) knowledge and concepts. This type of research is classroom action research using a qualitative approach. The study was conducted with 2 cycles in 2 (two) meetings. The research subjects were XI IPA1 SMA Sunan Kalijaga Jabung Malang. Data obtained in the form of observation sheets of student and teacher activities and tests of student learning outcomes each cycle. The results of this study are the achievement of improved PKn learning process as evidenced by the scor activity of students in the first cycle (3.1) interpreted active student activities, and cycle II obtaining scor (3.78) means that in the learning process students are very active. Observation of teacher activities also showed an increase with scor in the first cycle (3.1) which means that the teacher's activities in the learning process were in a good category, experienced an increase in cycle II with Scor (3.7) which was very good. Student learning achievement also increased with the value of the test cycle I amounting to (78.9) with the percentage of completeness (68.4%) increasing in the second cycle the test score was (86.3) with the percentage of completeness (92.1%). The conclusion is by applying the strategy of social inquiry learning in improving learning and learning achievement in PKn subjects.Â Keywords: learning process, learning achievement, social inquiry